To the question about the angle correction influence and cylindrical helical gear teeth wear on its longevity - Чернець, М.В; Чернець, Ю.М. (Problems of Tribology, 2014)
The angle correction influence of cylindrical helical gear on its longevity as the teeth are coming in and out of contact has been investigated. The regularities of longevity changes in accepted displacement coefficients’ range under constant contact pressures have been established. Also under the developed methodology the influence of teeth flexure radius changing influence has been taken into account in consequence of wear on longevity uncorrected and corrected gear.